94 ARE SERIAL LIVER BIOPSIES USEFUL IN ASSESSING DISEASE PROGRESSION IN INDIVIDUALS WITH PRIMARY BILIARY CIRRHOSIS?. (1st March 2005) - Saldana, S.; Mayo, M. J.; Frawley, W.; Butsch, R.; Combes, B.
Abstract : Introduction: Primary biliary cirrhosis (PBC) is a chronic autoimmune cholestatic liver disease that causes progressive hepatic fibrosis, often leading to liver failure. The severity of PBC is typically determined by grading the extent of fibrosis in a liver biopsy using a 4-point histological scale: 0 = no fibrosis, 1 = non-bridging fibrosis, 2 = bridging fibrosis, and 3 = cirrhosis. However, liver biopsy is prone to sampling error, and it is sometimes a painful and dangerous procedure. The utility of serial liver biopsies to detect disease progression has not been studied, but it is a critical issue for clinical investigators and physicians. Null Hypothesis: The average change of fibrosis in serial liver biopsies in patients with PBC is not a reliable indicator of clinical progression. Methods: Serial liver biopsies were collected every 2 years on 265 subjects with PBC as part of a multicenter double-blind randomized controlled study, which demonstrated that methotrexate, when added to ursodiol treatment, had no effect on PBC. Mean follow-up was 7.4 years, and 935 samples were collected. Four pathologists, who were blinded to the sample order, graded each biopsy. A mean fibrosis score was calculated for each biopsy. Clinical decompensation was defined as development of one or more of the following: varices, ascites, encephalopathy, variceal bleed, liver transplant or liver death. The rate of change of fibrosis over time was compared between the patients who experienced clinical decompensation (n = 83) and those who did not (n = 162) using the Wilcoxon rank sum test. Results: Fibrosis increased an average of 0.05 stages per year in the group who developed clinical decompensation and decreased 0.01 stages per year in the group who did not. This difference was statistically significant (p<.01). However, a cumulative proportions analysis revealed that fibrosis changed no more than 0.25 stages per year in 86% of individuals with clinical events and in 92% without events. Conclusion: In a large group of PBC patients, serial liver biopsies can detect a statistical difference in the change of fibrosis between patients who develop clinical decompensation versus patients who do not. However, the average rate of change in fibrosis associated with clinical decompensation is too small to be appreciated in an individual patient. Thus serial liver biopsies are not useful clinical tools to assess disease progression in individuals with PBC taking ursodiol.